2017
DOI: 10.1136/bmjgh-2017-000424
|View full text |Cite
|
Sign up to set email alerts
|

Effective coverage of primary care services in eight high-mortality countries

Abstract: IntroductionMeasurement of effective coverage (quality-corrected coverage) of essential health services is critical to monitoring progress towards the Sustainable Development Goal for health. We combine facility and household surveys from eight low-income and middle-income countries to examine effective coverage of maternal and child health services.MethodsWe developed indices of essential clinical actions for antenatal care, family planning and care for sick children from existing guidelines and used data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
90
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(98 citation statements)
references
References 42 publications
7
90
0
1
Order By: Relevance
“…Our results cast doubt on such an outcome in Burundi: overall, our study found a consistently poor level of adherence on IMCI guidelines by HWs, which is likely to affect the quality of care for their patients. This low compliance is consistent with evaluations of IMCI case management practices in several other settings [20][21][22][23] and other studies in the field of quality of care for sick children [24]. This finding indicates a missed opportunity to benefit Burundi's children given that some studies have reported that IMCI is associated with improvements in the quality of health care [25][26][27].…”
Section: Discussionsupporting
confidence: 82%
“…Our results cast doubt on such an outcome in Burundi: overall, our study found a consistently poor level of adherence on IMCI guidelines by HWs, which is likely to affect the quality of care for their patients. This low compliance is consistent with evaluations of IMCI case management practices in several other settings [20][21][22][23] and other studies in the field of quality of care for sick children [24]. This finding indicates a missed opportunity to benefit Burundi's children given that some studies have reported that IMCI is associated with improvements in the quality of health care [25][26][27].…”
Section: Discussionsupporting
confidence: 82%
“…Other studies have also found large gaps between coverage of care-seeking and effective or quality-adjusted coverage: for example Marchant et al found in 3 settings that quality coverage of ANC was 82%-93% lower than overall ANC coverage, and quality coverage of delivery was 41%-53% lower than overall coverage of institutional delivery [7]. Leslie et al found that across 8 countries, effective coverage of ANC was 44% lower than ANC4, and effective coverage of sick child care 62% lower than care-seeking for sick children [10]. These findings highlight the work that remains in ensuring that effective interventions, delivered with high quality, reach individuals in need.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, the WHO released guidelines that increased the recommended contacts to eight visits [10], although this has not yet been widely adopted as a measure of coverage. Studies on quality-adjusted coverage have used both one visit and four visits to quantify ANC coverage, which is based typically on maternal self-report in household surveys [11][12][13][14][15][16][17][18][19]. Facility measures have similarly followed WHO guidance on the expectations for ANC and have generally focused on inputs to care, with studies that define structural quality measures for health facilities such as functional diagnostics and medications [11,15,16].…”
Section: Viewpoints Research Theme 1: Countdown Coveragementioning
confidence: 99%